Rules of Engagement: The Why, What, and How of Professional Engagement for Pharmacy - Benjamin D. Aronson; Kristin K. Janke (University of Minnesota Libraries Publishing, 2015)
The development of student pharmacists must include inspiring within them a sense of engagement in their profession. This paper provides the rationale for and the potential implications of this concept, as well as an overview of experiences with professional engagement in student pharmacists at one college of pharmacy. Curricular-based experiences and research will be discussed, including the insights gained and suggestions for developing and encouraging professional engagement. Lastly, this article provides future direction for furthering professional engagement on both the conceptual and curricular level.   Type: Idea Paper